Komparasi Motivasi dan Hasil Belajar Mahasiswa Menggunakan Model Kooperatif Tipe GI dan Tipe STAD - Rahayu, Ayu; Rosti, Rosti; Adewia, Musdalifatul (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Students must own motivation as a driver of the learning process in order to improve their learning outcomes. This study aims to compare students’ motivation and learning outcomes using the GI and STAD models. The study adopted a quasi-experimental study with a nonequivalent control group design. Given that the research population was 40 students who took education management courses, the sampling technique used was saturated sampling where all populations were used as research samples. Class A (GI model) and B (STAD model) each amounted to 20. This study used a questionnaire instrument to measure learning motivation and a description test to measure learning outcomes. Prior to the usage of the test, a trial was conducted to determine its validity and reliability. The results of the descriptive analysis obtained almost the same mean, STAD (3.27) and GI (3.01) learning motivations had a difference of 0.26, while the mean STAD (82.75) and GI (80.15) learning outcomes had a difference of 2.60. The prerequisite test, which shows motivation data and learning outcomes, are normally distributed and homogeneous. Testing the hypothesis with the Paired Sample T-Test revealed a small difference in student motivation and learning outcomes in the application of the GI and STAD models. In conclusion, it can be surmised that STAD and GI models can improve student motivation and learning outcomes. Therefore, STAD and GI models can be used in learning, especially in education management courses.